Human immunodeficiency virus type 1 Vpu protein induces rapid degradation of CD4. - Willey, R L (1992)
CD4 is an integral membrane glycoprotein which is known as the human immunodeficiency virus (HIV) receptor for infection of human cells. The protein is synthesized in the endoplasmic reticulum (ER) and subsequently transported to the cell surface via the Golgi complex. HIV infection of CD4+ cells leads to downmodulation of cell surface CD4, due at least in part to the formation of stable intracellular complexes between CD4 and the HIV type 1 (HIV-1) Env precursor polyprotein gp160. This process "traps" both proteins in the ER, leading to reduced surface expression of CD4 and reduced processing of gp160 to gp120 and gp41. We have recently demonstrated that the presence of the HIV-1-encoded integral membrane protein Vpu can reduce the formation of Env-CD4 complexes, resulting in increased gp160 processing and decreased CD4 stability. We have studied the effect of Vpu on CD4 stability and found that Vpu induces rapid degradation of CD4, reducing the half-life of CD4 from 6 h to 12 min. By using a CD4-binding mutant of gp160, we were able to show that this Vpu-induced degradation of CD4 requires retention of CD4 in the ER, which is normally accomplished through its binding to gp160. The involvement of gp160 in the induction of CD4 degradation is restricted to its function as a CD4 trap, since, in the absence of Env, an ER retention mutant of CD4, as well as wild-type CD4 in cultures treated with brefeldin A, a drug that blocks transport of proteins from the ER, is degraded in the presence of Vpu.